THE APPLICATION OF STEM-BASED IPA LEARNING ACTIVITIES TO IMPROVE LEARNING MOTIVATION IN STRAIGHT MOTION CONCEPTS IN JUNIOR HIGH SCHOOL - Lintang Nurul Fatichah; Ida Kaniawati; Agus Jauhari (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2019)
ABSTRACT Parents are the most influential figure in the life of every child. Parental involvement in the learning process can also affect the process of life is huge in children. In addition, the teachers and the learning environment in schools can also influence the motivation to learn so that students can master the student's mastery of concepts in science lessons in schools, especially physics known as a difficult subject among junior high school students. Therefore teachers and learning environments should be supportive atmosphere so that students more motivated to follow the lessons of Natural Sciences. The purpose of this study was to determine the increase in student motivation by using STEM-based science learning. This study uses a quantitative research with the participation of as many as 28 students of class VIII-5 on one of the Junior High School in Bandung. The instrument used in this study was a questionnaire on aspects of learning motivation Need for Achievement, Need for Power aspects, and aspects of the Need for Affiliation. The results showed that the students' motivation to learn the most improved there on aspects Need for Power showed an increase by a margin of 3.53 and an average pretest and posttest of 0.89. It can be concluded that the application of STEM-based science learning can increase students' motivation. Solutions to increase learning motivation towards science subjects can use based learning Science, Technology, Engineering, and Mathematics (STEM). Keywords: Motivation; STEM.